ANALISIS SEMIOTIKA PESAN DAKWAH DALAM FILM CINTA SUBUH KARYA INDRA GUNAWAN - Apriliyana Apriliyana (Jurnal Komunikasi, 2023)
Cinta Subuh is an Indonesian film in 2022 directed by Indra Gunawan. This film, based on a novel by Ali Farighi, stars Dinda Hauw, Roger Danuarta and Rey Mbayang. The film Cinta Subuh will be released in theaters on May 19, 2022. The type of research used is a qualitative approach where this type of research seeks to collect facts, data or information and explore facts, data and information with certain scientific techniques. The data analysis technique used is media text analysis with Charles Sanders Pierce's semiotic analysis model. Based on the results of research conducted on "Semiotic Analysis of Da'wah Messages in the Film Cinta Subuh by Indra Gunawan" there are three symbols of da'wah messages depicted in the film. That is, the message of preaching morality includes the behavior of a person who is driven by a conscious desire to do a good deed. Sharia da'wah messages include Allah's laws which are established based on the arguments of the Qur'an and Sunnah and the Aqidah da'wah messages include faith or belief that is certain without the slightest doubt about the basics of Islamic teachings given by the Al-Qur'an and Hadith . Where the three symbols of the da'wah message above are analyzed using Charles Sanders Pierce's semiotic analysis approach, namely studying the meaning of signs using three elements of objects, signs and independent